Green tea polyphenols mitigate the plant lectins-induced liver inflammation and immunological reaction in C57BL/6 mice via NLRP3 and Nrf2 signaling pathways. (October 2020) - Wang, Dongxu; Zhang, Man; Wang, Taotao; Liu, Tiantian; Guo, Yuanxin; Granato, Daniel
Abstract: Plant-derived dietary lectins have been reported to be involved in the pathogenesis of several inflammatory diseases, including hepatitis, inflammatory bowel disease, diabetes, and celiac disease. In this present study, we aimed to assess whether green tea polyphenols (GTPs) exerts protective effects against plant lectins-induced liver inflammation and immunological reaction in mice. The C57BL/6 mice received intragastric GTPs (200 mg/kg b.w.) once per day for 7 consecutive days prior to plant lectins stimulation (50 mg/kg b.w., intraperitoneally). GTPs supplementation alleviated the histopathological changes of liver and the disorder of serum biochemical parameters in plant lectins-challenged mice. GTPs supplementation also alleviated plant lectins-induced oxidative stress and liver inflammation, decreasing protein contents and gene expression levels of pro-inflammatory cytokines in the plasma and hepatic tissue and increasing antioxidant capacity in the liver. GTPs decreased the protein expression levels of myeloperoxidase, F4/80 and neutrophil, as determined by immunohistochemical analysis, and T lymphocytes (CD4 and CD8) contents as determined by immunofluorescence analysis, in the liver. Moreover, we found that GTPs inhibited Nod-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome expression and increased nuclear factor erythroid 2-related factor 2 (Nrf2) pathways in the liver tissues of plant lectins-challenged mice. Taken together, these results show that GTPs alleviates hepatic inflammatory damage and immunological reaction after plant lectins challenge, and GTPs (or green tea intake) supplements can be beneficial for people exposed to plant lectins. Highlights: GTPs ameliorated plant lectins-induced inflammation and increasing antioxidant capacity in the liver. GTPs alleviated the histopathological changes in plant lectins-challenged mice. GTPs decreased the expression of MPO, F4/80, neutrophil and T lymphocytes in plant lectins-challenged mice. GTPs inhibited NLRP3 inflammasome activation and increased Nrf2 pathway in the liver.